THE USE OF COMIC BOOK IN TEACHING READING COMPREHENSION OF NARRATIVE TEXT - Aini, Rizka Marlisa; Ananda, Dinni Melisza; Keumala, Meta (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study investigates the impact of incorporating comic books into teaching narrative texts on the academic performance of first-grade students at SMA 9 Banda Aceh. Employing a pre-test and post-test design along with a detailed questionnaire, the research highlights consistent improvements in students’ comprehension and motivation. A significant result includes a score increase from 60 to 85 for one student, with an average N-Gain score of 58.43% and a maximum N-Gain score of 75.00%. These findings demonstrate the effectiveness of comic books in enhancing students’ understanding of narrative texts. The questionnaire results further support these outcomes, revealing high levels of student satisfaction, ease of comprehension, and increased enthusiasm for learning English. Students reported that the use of comic books made lessons more engaging and accessible. Despite facing minor challenges in implementation, the overall positive responses underscore the benefits of this teaching approach, including heightened motivation and improved comprehension. The study concludes that integrating comic books into English lessons is an effective pedagogical strategy for improving students’ understanding of narrative texts. It emphasizes the potential of comic books to make learning more interactive and enjoyable, offering innovative methods for strengthening students’ English language foundations. This research contributes to the growing body of evidence supporting creative and student-centered teaching techniques in education.